A Rare Diagnosis in the Neck During Childhood: Congenital Chondrolipoma - Fulya ÖZER; Nebil BAL (Federation of Turkish Pathology Societies, 2017)
Chondrolipomas are mesenchymal tumors that found as mature cartilage tissue in a fat tissue. A 2-year-old boy was seen with a complaint of a mass of the neck. On physical examination of the child, there was a one-centimeter mass above the sternocleidomastoid muscle on the lateral neck. Pathological examination of this mass after excision was reported as chondrolipoma. Chondrolipomas are seen mostly in the breast and in the adult. They are rare tumors of the head and neck area and seen mostly the in oral cavity here. This is the first case of chondrolipoma with this age and localization combination in the literature. Chondrolipoma should therefore also be considered in the differential diagnosis of congenital masses located at lateral cervical area.